2004
DOI: 10.1021/np0304823
|View full text |Cite
|
Sign up to set email alerts
|

New Stilbene Derivatives from Calligonum leucocladum

Abstract: Two new stilbene derivatives, (E)-resveratrol 3-(6' '-galloyl)-O-beta-D-glucopyranoside (1) and (E)-resveratrol 3-(4' '-acetyl)-O-beta-D-xylopyranoside (2), and five known stilbene derivatives (3-7) were isolated from the dried aerial parts of Calligonum leucocladum. Their structures were established on the basis of spectroscopic evidence. Compound 1 showed antioxidant activity and a restorative effect of the inhibition of oxacillin to oxacillin/methicillin-resistant Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…In addition, we found that resveratrol 3-(6Љ-galloyl)-O-␤-Dglucopyranoside possessed ILSMR activity, while resveratrol 3-(4Љ-acetyl)-O-␤-D-glucopyranoside did not (26). These results are indicative of a feature common to the molecular structures of all the ILSMRs listed above: a lipophilic portion is connected via an ester linkage to the galloyl group bearing the polar hydroxyl groups.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, we found that resveratrol 3-(6Љ-galloyl)-O-␤-Dglucopyranoside possessed ILSMR activity, while resveratrol 3-(4Љ-acetyl)-O-␤-D-glucopyranoside did not (26). These results are indicative of a feature common to the molecular structures of all the ILSMRs listed above: a lipophilic portion is connected via an ester linkage to the galloyl group bearing the polar hydroxyl groups.…”
Section: Discussionmentioning
confidence: 68%
“…17 Acetylated derivatives of polyphenols can be found in natural sources such as plants. [18][19][20][21] The ability of acetylated polyphenols to promote tumor cell cycle arrest, death and to sensitize them to other anticancer agents remained to be explored. In the present study, we compare the effects of trans-resveratrol obtained from vine shots (R), the acetylated form of trans-resveratrol (trans-resveratrol triacetate, R3A), the resveratrol oligomer e-viniferin (eV) and its penta-acetate derivative (eV5A) and the vineatrol preparation (Vinea).…”
mentioning
confidence: 99%
“…It is usually not known if the analysed samples have been healthy or had been stressed. Resveratrol has also been identified in many medicinal plants, such as Calligonum leucocladum (Okasaka et al, 2004), Cassia quinquangulata, C. garrettiana (Hata et al, 1979;Pezzuto, 2011), Erythropleum lasiantum (Orsini et al, 1997), Ficus barteri fruits (Ogungbamila et al, 1997), Reynoutria japonica (Kimura et al, 1995), Polygonum cuspidatum (Jayatilake et al, 1993;Vastano et al, 2000), and Smilax glabra (Chen et al, 1999). Paul et al (1999) demonstrated that darakshasava, an ayurvedic medicine from India, which main ingredient is Vitis vinifera, contains resveratrol and pterostilbene.…”
Section: Other Products Containing Stilbenesmentioning
confidence: 99%